Film availability in Netflix country stores in the EU - Michail Batikas; Estrella Gomez-Herrera; Bertin Martens (European Commission, Joint Research Centre (JRC), 2015)
This study compares the film catalogues among the 11 Netflix country stores in the EU that provide film streaming services to consumers on the basis of a subscription (SVOD) business model. We estimate cross-border availability of films in Netflix in the EU at 31%, somewhat lower than the 40% availability of downloadable films in the Apple iTunes stores in the EU. Availability patterns are to a large extent driven by consumer preferences and geographical and linguistic proximity. The average delay in availability between theatre and Netflix release (“windowing”) in the EU11 is 326 days, with wide variations across countries, compared to only 112 days delay in the US. Windowing delays are shortening for more recent films. For a sample of films in the UK Netflix catalogue we find that they remain available for 340 days on average.
Keywords: F15; 330; Netflix; digital film; video on demand; VoD; film catalogues